2022
DOI: 10.3390/atmos13010108
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Severe Sand and Dust Storm Event in March 2021 in Northern China: Dust Emission Schemes Comparison and the Role of Gusty Wind

Abstract: Northern China experienced a severe sand and dust storm (SDS) on 14/15 March 2021. It was difficult to simulate this severe SDS event accurately. This study compared the performances of three dust-emission schemes on simulating PM10 concentration during this SDS event by implementing three vertical dust flux parameterizations in the Comprehensive Air-Quality Model with Extensions (CAMx) model. Additionally, a statistical gusty-wind model was implemented in the dust-emission scheme, and it was used to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In particular, the KOK14 scheme simulates more (less) emission over Taklimakan desert (northeastern China) than the MB95 scheme (Figure 12D; Supplementary Figure S8), which is more consistent with MERRA-2 and CAMS-F. The better performance of the KOK14 scheme has been demonstrated in Kok et al (2014) and has been shown in previous studies that the KOK14 scheme tends to predict more dust emission than the MB95 scheme during the Asian dust storm event (Wu et al, 2019;Zeng et al, 2020;Wang et al, 2022) and thus shows better agreement with observation. This can be linked to the high sensitivity of dust flux in the KOK14 scheme to the soil's threshold friction velocity, as it accounts for soil's increased ability to produce dust under continuous saltation bombardment, taking also into account an increased scaling of the vertical dust flux with wind speed (Kok et al, 2014).…”
Section: Underestimation Of Dust Emission and Concentration In Flexdu...supporting
confidence: 74%
See 3 more Smart Citations
“…In particular, the KOK14 scheme simulates more (less) emission over Taklimakan desert (northeastern China) than the MB95 scheme (Figure 12D; Supplementary Figure S8), which is more consistent with MERRA-2 and CAMS-F. The better performance of the KOK14 scheme has been demonstrated in Kok et al (2014) and has been shown in previous studies that the KOK14 scheme tends to predict more dust emission than the MB95 scheme during the Asian dust storm event (Wu et al, 2019;Zeng et al, 2020;Wang et al, 2022) and thus shows better agreement with observation. This can be linked to the high sensitivity of dust flux in the KOK14 scheme to the soil's threshold friction velocity, as it accounts for soil's increased ability to produce dust under continuous saltation bombardment, taking also into account an increased scaling of the vertical dust flux with wind speed (Kok et al, 2014).…”
Section: Underestimation Of Dust Emission and Concentration In Flexdu...supporting
confidence: 74%
“…FLEXPART using the output of FLEXDUST-update yields comparable results to MERRA-2 and CAMS-F, and similar to the two dataset, it still underestimates the observed peak of surface PM 10 (by an order of magnitude at some sites) during the dust storm event (Figure 5). It is also noticed that studies using the meso-scale model WRF-CHEM and an offline chemical transport model CAMx also exhibit a similar magnitude of underestimation of surface PM 10 during Frontiers in Environmental Science frontiersin.org the East Asian dust storm events using their default settings (Song et al, 2019;Wang et al, 2022). The underestimation of the observed surface PM 10 peak during the dust storm event can be largely ascribed to the underestimation of the dust emission in the models.…”
Section: Underestimation Of Dust Emission and Concentration In Flexdu...mentioning
confidence: 75%
See 2 more Smart Citations
“…Cheng et al (2012) explained the mechanism of soil erosion and sand entrainment by the coherent structure of wind gusts by means of Lattice Boltzmann Method. The implementation of the gust-wind model could help improve the simulation performance in the concentration of PM 10 during severe sand and dust storms (Wang et al 2022). Models for dust storm forecasting could be improved by utilizing atmospheric humidity and wind speed as the main drivers for dust generation and transport (Csavina et al 2014).…”
Section: Introductionmentioning
confidence: 99%